Suspected Acute Respiratory Distress Syndrome Associated With the Use of Intravenous Lipid Emulsion Therapy in a Dog: A Case Report - Botha, Heike; Jennings, Samuel Hollis; Press, Saya A.; Istvan, Stephanie A. (Frontiers in Veterinary Science, 2019)
A 12-year-old male neutered Bichon Frise presented to the Emergency Department for stupor and bradycardia after ingestion of chocolate covered 450 mg (90 mg/kg) tetrahydrocannabinol. The patient was hospitalized for supportive care, IV fluid therapy and monitoring in the intensive care unit. During hospitalization the patient became comatose and bradypneic. Treatment with intravenous lipid emulsion (ILE) therapy was instituted to accelerate toxin elimination, reduce the risk of complications related to progressive obtundation and shorten hospitalization time. Five hours after infusion, the patient developed severe respiratory distress and was ultimately euthanized. Post-mortem histologic evaluation of lung revealed severe pulmonary edema consistent with acute respiratory distress syndrome. There are infrequent reports of adverse effects associated with ILE therapy for toxicosis in veterinary medicine despite reports of complications such as acute respiratory distress syndrome in human literature. The purpose of this report is to describe the potential for a severe adverse event after treatment of a toxicosis with ILE therapy.